MARK AS NARRATIVE (Plot and Structure of Mark 4,35-8,30) - Ferry Hartono (STIKAS Santo Yohanes Salib Kalimantan Barat, 2018)
Every literature consists of Story and Plot, or should I say, series of events. While the Story is about what happened literally, the Plot is more about how the narrator explains what happened. Aristotle alleged that the Plot and Structure were the most important elements in of a Tragedy (Poetics VI,5; VII,1). However, the success of a story also depends on the rendering of Character (Poetics VI,5). Therefore, the study about Characters in Narrative Criticism is necessary to conclude the exploration of a literature. Gospel of Mark, as presented in this paper is through and through a story. Study of plot and structure in it, therefore, is necessary to build the sufficient base for study of character. This research paper is dedicated mainly on plot of the Gospel of Mark, particularly Mark 4,35-8,30. To understand the plot, it is essential to know the style and context of the literature at hand, facts about the author and the setting of the story.